2022
DOI: 10.1177/13524585221134216
|View full text |Cite
|
Sign up to set email alerts
|

T cell responses to COVID-19 infection and vaccination in patients with multiple sclerosis receiving disease-modifying therapy

Abstract: Background: Multiple sclerosis (MS) is a neurological disorder marked by accumulating immune-mediated damage to the central nervous system. The dysregulated immune system in MS combined with immune effects of disease-modifying therapies (DMTs) used in MS treatment could alter responses to infections, including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes coronavirus disease 2019 (COVID-19). Most of the literature on immune response to SARS-CoV-2 infection and COVID-19 vaccination, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 65 publications
(131 reference statements)
1
12
0
Order By: Relevance
“…Similar findings were reported by other studies that observed robust cellular response to the COVID-19 vaccine in the majority of patients on teriflunomide and other DMTs, except for S1P modulators [28,44]. S1P modulators reduce both B-and T-cell responses, while anti-CD20 therapies reduce B-cell-mediated response [15,17].…”
Section: Immune Response To Sars-cov-2 Infectionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar findings were reported by other studies that observed robust cellular response to the COVID-19 vaccine in the majority of patients on teriflunomide and other DMTs, except for S1P modulators [28,44]. S1P modulators reduce both B-and T-cell responses, while anti-CD20 therapies reduce B-cell-mediated response [15,17].…”
Section: Immune Response To Sars-cov-2 Infectionsupporting
confidence: 89%
“…In general, the most recent data do not support the increased risk of worse COVID-19 outcomes related to patients on DMTs [6, 29, 36]. Some studies even suggested the potential beneficial effect of INF and glatiramer acetate that were associated with a lower risk of contraction in COVID-19 [1, 6, 9, 14, 16, 17]. Several authors agreed that teriflunomide could have a beneficial effect against COVID-19 too, since it may prevent an excessive host immune response [23].…”
Section: Covid-19 In People With Msmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Patients taking B-cell depleting therapy or an S1P modulator may mount an attenuated response to vaccines compared with patients who are not taking these medications. 64,65 Some DMTs may require special timing considerations regarding when to obtain a vaccine. It is recommended by the NMSS that PwMS undergo COVID-19 vaccination; all COVID-19 vaccines available in the US are safe for PwMS.…”
Section: ■ Social Concernsmentioning
confidence: 99%
“…Patients receiving immunosuppressive or immunomodulating DMTs should avoid live vaccines, and patients should not receive a vaccine while experiencing a relapse 63. Patients taking B-cell depleting therapy or an S1P modulator may mount an attenuated response to vaccines compared with patients who are not taking these medications 64,65. Some DMTs may require special timing considerations regarding when to obtain a vaccine.…”
Section: Implications For the Primary Care Providermentioning
confidence: 99%